2020
DOI: 10.18332/tid/127231
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco use and other aspects related to smoking among school-going adolescents aged 13–15 years in Malaysia: Analysis of three cross-sectional nationally representative surveys in 2003, 2009 and 2016

Abstract: disease having been a major contributor to mortality since 1980 3 , with a third of diseases due to smoking 4. Several nationwide studies have reported that more than 70% of smokers started to smoke before the age of 18 years; this is in line with other studies conducted ABSTRACT INTRODUCTION Periodic surveys on tobacco use patterns and other aspects of tobacco use among school-going adolescents in Malaysia provide information on the effectiveness of anti-smoking measures implemented. However, such information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Therefore, the use of any tobacco product or other form of tobacco product by this group is the norm. Moreover, Malaysian society still holds on to traditions wherein the social norms governing female behavior may attribute to the reduced involvement of female respondents in smoking cigarettes and other tobacco products 2 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the use of any tobacco product or other form of tobacco product by this group is the norm. Moreover, Malaysian society still holds on to traditions wherein the social norms governing female behavior may attribute to the reduced involvement of female respondents in smoking cigarettes and other tobacco products 2 .…”
Section: Discussionmentioning
confidence: 99%
“…This is expected to continue given the current trend, i.e. plateau in adult smoking prevalence, with small reduction in teen smoking prevalence over the past decade 2 . Studies have shown that smoking is a behavior initiated during adolescence 3 .…”
Section: Introductionmentioning
confidence: 96%
“…The inaugural GYTS revealed that 20.2% of 13 to 15-year-old adolescents (36.3% males) and (4.2% females) smoked in 2003; however, an 18.2% decrease in active adolescent smokers was reported in 2009. In Malaysia, a more recent study depicted that 14.2% of 10 to 19-year-old adolescents smoked with a prevalence of 24.3% and 3.7% in males and females, respectively [8].…”
Section: Introductionmentioning
confidence: 99%